Kontribusi fiskal daerah terhadap peningkatan kesejahteraan masyarakat: Studi Kasus Provinsi Jawa Tengah - Zulianissa Diah Kusmawati; Naila Tamaamil Atsnaa; Umi Masruroh; Puji Astuti; Lucia Rita Indrawati; Syifaur Rahmah (Journal of Economics Research and Policy Studies, 2025)
The main problem of this study lies in how fiscal contributions through local taxes, transfers, and expenditures can genuinely enhance community welfare. In fact, the effectiveness of public fund utilization has not been optimal, resulting in a less-than-maximum impact on human development. This study aims to analyze the contribution of regional fiscal policy to improving community welfare in Central Java Province during the 2021–2023 period. The Human Development Index (HDI) is used as an indicator of welfare, focusing on the effects of regional taxes, intergovernmental transfers, and regional expenditures. A quantitative approach is employed using panel data regression analysis with the Fixed Effect Model (FEM). The results show that simultaneously, all three independent variables have a significant effect on the HDI. However, partially, only regional taxes and regional expenditures significantly influence the HDI, while intergovernmental transfers do not have a significant effect. These findings indicate that the effectiveness of public fund utilization has not yet been optimal in supporting human development. Therefore, more targeted fiscal management is needed to ensure that fiscal outcomes have a real impact on community welfare.